Tshenguluso ya ndeme ya nyaluwo ya luambo lwa Tshivenda yo tutuwedzwayo nga mupindulelo wa maipfi - Nangambi, Noria Ntshengedzeni (University of Limpopo, 2012)
The study dealt with enrichment of Tshivenḓa language through adoption of words from other languages such as English, Afrikaans, Sotho, Tsonga, Zulu and many more. The study discovered that no language can remain static forever and this applies to Tshivenḓa as well. Every successive generation makes its own small contribution to language change and when sufficient time has elapsed the impact of these changes becomes more obvious. It however cautions that borrowing of words should not be overdone as this may lead to the disappearance of Tshivenḓa as we know it.
Thesis (M.A.) --University of Limpopo, 2012
Keywords: Adoption of words; Venda language; Venda language; Venada language -- Foreign words and phrases